Microbial and Physico-Chemical Quality Assessment of Rivers of Kathmandu Valley - Poudel, Santosh; Paudyal, Akash; Sharma, Bishnu Prasad; Sharma, Kamana; Baral, Yubaraj; Adhikari, Shailaja; Shakya Hada, Manju Shree (Nepal Journal of Biotechnology, 2021)
Water quality refers to the chemical, physical, biological characteristics of water. It is a measure of condition of water relative to requirement of one or more biotic species and or to any human need or purpose. The main objective of the study is to detect the physio-chemical and microbiological parameters of water sample from the Bagmati river and its tributaries of Kathmandu valley along with antibiotic susceptibility. In physico-chemical parameters, turbidity, temperature, pH, Electrical conductivity, Dissolved Oxygen, Biological Oxygen Demand, Ammonia, Alkalinity, Hardness, Chloride, Phosphate, Iron, Nitrate, Total Dissolved solids, and color were analyzed. Iron and Turbidity was found to be above the World health organization and Nepal Standard guideline in all the samples (100%), while Ammonia was found to be above the WHO guideline in 10(90%) samples. Among 11 samples, 10(90%) showed a low Dissolved oxygen level. Most Probable Number method was followed for counting total load of coliform and fecal coliform. Escherichia coli was isolated from the sample and subjected to Antibiotic susceptibility. Coliform was detected in all the samples and E. coli was identified as highly resistant towards Gentamicin (81.8%) and sensitive towards Chloramphenicol (81.8%). High value of ammonia, turbidity and low value of Dissolved Oxygen in the lower belts of river was due to large inputs of wastewater and organic loads caused by anthropogenic activities. High value of Coliform in all the samples indicates bacterial contamination in river water. The comparative study for the water quality variables in the urban areas showed that the main rivers and its tributaries were equally polluted.